Евгений Онегин: роман в стихах / А. С. Пушкин - Пушкин Александр Сергеевич (Школьная библиотека, 1980)
Экземпляры: ф. 2 (20200515) / Инвентарный номер: 111909 / Цена: 10.00 / Авт.знак: П 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1